Mengukur Keamanan Siber Indonesia Melalui Indikator Pilar Kerjasama Dalam Global Cybersecurity Index (GCI) - Feline Cloramidine; Muhammad Badaruddin (Universitas Nasional, 2023)
The revolution of digital technology has changed the landscape of international relations. Communication patterns between countries are becoming more transparent, multi-channel, and involving various parties with dynamic participation from non-state actors. These changing conditions benefit our lives while bringing new challenges that must be managed together internationally. This study discusses Indonesia's ability to manage its cyberspace which is assessed through the Global Cybersecurity Index (GCI) variable. Researchers are interested in analyzing Indonesia's commitment in meeting GCI guidelines, especially on indicators from the pillars of international cooperation that have succeeded in obtaining maximum assessment points from Indonesia's GCI score. Although, from some of the indicators mentioned it is not clearly illustrated whether it is achieved well or not. This research was conducted with qualitative methods, especially case studies to analyze cases systematically and also literature study data collection techniques. To achieve this goal, this article prepared by describing the importance of the pillars of international cooperation in improving Indonesia's global cybersecurity index score in the first part. Then we presented a map of cyberattacks against Indonesia from 2018 to 2020 and compared it with the increase in Indonesia's GCI score in the same period. This paper also describe the dynamics of relations between Indonesian ministries and institutions with their international partners for the third part. Finally, in the fourth part, this paper examine the advantages and disadvantages of Indonesia's efforts to improve the performance of its international cooperation in order to improve the level of its cybersecurity.' Revolusi teknologi digital telah mengubah lanskap hubungan internasional. Pola komunikasi antar negara menjadi lebih transparan, multi-channel, dan melibatkan berbagai pihak dengan partisipasi yang dinamis dari aktor non-negara. Kondisi yang berubah ini menguntungkan kehidupan kita sekaligus membawa tantangan baru yang harus dikelola bersama secara internasional. Penelitian ini membahas tentang kemampuan Indonesia dalam mengelola ruang sibernya yang dinilai melalui variabel Global Cybersecurity Index (GCI). Peneliti tertarik untuk menganalisis komitmen Indonesia dalam memenuhi pedoman GCI, khususnya pada indikator-indikator dari pilar kerjasama internasional yang berhasil mendapatkan poin penilaian maksimal dari skor GCI Indonesia. Meskipun, dari beberapa indikator yang disebutkan tidak tergambar dengan jelas apakah tercapai dengan baik atau tidak. Penelitian ini dilakukan dengan metode kualitatif, khususnya studi kasus untuk menganalisis kasus secara sistematis dan juga teknik pengumpulan data studi kepustakaan. Untuk mencapai tujuan tersebut, artikel ini disusun dengan menggambarkan pentingnya pilar kerjasama internasional dalam meningkatkan skor indeks keamanan siber global Indonesia pada bagian pertama. Kemudian kami memaparkan peta serangan siber terhadap Indonesia dari tahun 2018 hingga 2020 dan membandingkannya dengan peningkatan skor GCI Indonesia pada periode yang sama. Tulisan ini juga menggambarkan dinamika hubungan kementerian dan lembaga Indonesia dengan mitra internasionalnya untuk bagian ketiga. Terakhir, pada bagian keempat, makalah ini mengkaji apa keuntungan dan kerugian yang didapatkan dari upaya Indonesia dalam meningkatkan kinerja kerjasama internasionalnya dalam rangka meningkatkan tingkat keamanan sibernya.